Protective Effect of Grape Seed Proanthocyanidins on Oxidative Damage of Chicken Follicular Granulosa Cells by Inhibiting FoxO1-Mediated Autophagy - Zhou, Shuo; Zhao, An; Wu, Yangyang; Mi, Yuling; Zhang, Caiqiao (Frontiers in Cell and Developmental Biology, 2022)
A significant decrease in poultry egg production occurs due to ovarian aging and autophagy is one of the important factors of ovarian aging that is induced predominantly by oxidative stress. Increasing evidence showed potential roles of plant-derived grape seed proanthocyanidin (GSPs) in protecting ovarian granulosa cells (GCs) from oxidative damage, although the underlying mechanism is still unclear. Here we investigated the possible functions of autophagy involved in the preventive effect of GSPs on oxidative stress in the GCs of ovarian hierarchical follicles of laying chickens. The results showed that increased autophagy was observed in the aging hens (580-day-old, D580) compared with the peak-lay hens (D280). Treatment of GSPs significantly restored the elevated autophagy and decreased viability of cultured D280 chicken GCs that were elicited by hydrogen peroxide. GSPs also suppressed the increased autophagy in the natural aging hens. Similar to the effect of GSPs on GC viability, inhibition of autophagy also showed a protective effect on the decreased viability of GCs under oxidative damage. However, GSPs were not able to provide further protection in GCs that were pretreated with 3-methyladenine (an autophagy inhibitor). In addition to its promoting action on antioxidant capacity, treatment with GSPs increased survival of GCs from autophagy that was caused by oxidative stress through the FoxO1-related pathway. Inhibition of FoxO1 or activation of PI3K-Akt pathway by GSPs increased the confrontation of GCs to oxidative damage and decreased autophagy in GCs. In addition, activation of the SIRT1 signal inhibited the GCs autophagy that was caused by oxidative stress via GSPs-induced deacetylation of FoxO1. These results revealed a new mechanism of GSPs against oxidative stress of GCs via inhibiting FoxO1, which was probably a possible target for alleviating ovarian aging in laying poultry.